ANALYSIS OF THE INFLUENCE OF TASTE, SERVICE QUALITY AND PRODUCT QUALITY ON CUSTOMER SATISFACTION AT FOX COFFEE JEMBER - Falina, Askia Salsabila; Setianingsih, Wahyu Eko; Murtaliningtyas, Wenny (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
In the beginning, many parents enjoyed coffee with a mixture of black coffee without sugar which we usually called Ireng coffee. This Fox Coffee Jember shop can serve orders online due to the increasingly rapid development of technology. They collaborate with Grabfood and Gofood which makes it easier for customers to order from home. This shows that the Fox Coffee Jember shop always follows developments and trends in society. The type of research used in this research is quantitative. The population in this study were Fox Coffee Jember customers and the sample taken was 85 people with a sampling technique using purposive sampling. Data collection methods are observation and questionnaires via Google Form. The data analysis used is multiple linear regression, while hypothesis testing uses the t test. The research results show that the dimensions of taste, product quality and service quality have a significant effect on customer satisfaction at Fox Coffee Jember. Suggestions for future researchers are adding variables that support measuring customer satisfaction such as price, cost and emotion variables so that they can provide a broader picture of what factors influence customer satisfaction.